NALP3 Q705K Gene Polymorphism Frequency in Behcet's Disease Patients in Turkey - DİRESKENELİ, RAFİ HANER (TURKISH SOC IMMUNOLOGY, 2016)
Objectives: This study aims to investigate Q705K polymorphism in NALP3 gene in Behcet's disease (BD). Patients and methods: This case-control study included 180 BD patients (92 males, 88 females; mean age 36.6 +/- 11.3 years; range 21 to 56 years) and 168 healthy controls (92 males, 76 females; mean age 34.9 +/- 13.2 years; range 22 to 55 years). Cellular deoxyribonucleic acid was isolated from peripheral blood using standard procedures. Patients and the controls were genotyped by polymerase chain reaction-restriction fragment length polymorphism method for NALP3 Q705K gene polymorphism. Polymorphic region was amplified by polymerase chain reaction and digested with BsgI enzyme. Genotype frequencies between the groups were compared by K2-square, Fisher's exact, and chi-square tests. Results: All BD patients had oral ulcers. Of the patient group, genital ulcers were present in 78%, folliculitis in 66.3%, vascular involvement in 31.2%, uveitis in 66.1%, and neurological manifestations in 7.5%. Of the control group, homozygous genotype was present in 1.2% (n=2) and heterozygous genotype in 11.3% (n=19), whereas of the patient group, homozygous genotype was present in 1.1% (n=2) and heterozygous genotype in 8.3% (n=16), without a statistically significant difference between the groups. Comparison of allele frequencies between two groups did not reveal a statistically significant difference (5.5% and 6.8%, respectively). Subgroup analysis according to ocular, mucocutaneous, vascular, articular, and neurologic involvement also revealed no statistical differences. Conclusion: According to our findings, distribution of NALP3 Q705K gene polymorphism shows no significant difference between patient and control groups in terms of disease susceptibility and system involvements in BD in Turkey.
Keywords: Behcet's disease; NALP3; NLRP3 gene; Q705K gene polymorphism; single nucleotide polymorphism; INFLAMMASOME; SUSCEPTIBILITY; ASSOCIATION; SEVERITY; GOUT